Self-care and adherence to medication: a survey in the hypertension outpatient clinic - Lip Gregory YH; Beevers D Gareth; Greenfield Sheila M; Gohar Faekah; Jolly Kate (BMC, 2008)
Abstract Background Self-care practices for patients with hypertension include adherence to medication, use of blood pressure self-monitoring and use of complementary and alternative therapies (CAM) The prevalence of CAM use and blood pressure self-monitoring have not been described in a UK secondary care population of patients with hypertension and their impact on adherence to medication has not been described. Adherence to medication is important for blood pressure control, but poor adherence is common. The study aimed to determine the prevalence of self-care behaviours in patients attending a secondary care hypertension clinic. Methods Cross-sectional questionnaire survey. 196 patients attending a secondary care hypertension clinic in a teaching hospital serving a multiethnic population, Birmingham, UK. Main outcome measures: Prevalence of use of CAM, home monitors, adherence to anti-hypertensive medication. Results CAM use in previous 12 months was reported by 66 (43.1%) respondents. CAM users did not differ statistically from non-CAM users by age, gender, marital status or education. Vitamins, prayer a dietary supplements were the most commonly used CAM. Nine (12.7%) women reported using herbal CAM compared to one man (1.2%), (p = 0.006). Ten (6.7%) respondents reported ever being asked by a doctor about CAM use. Perfect adherence to anti-hypertensive medication was reported by 26 (44.8%) CAM-users and 46 (60.5%) non-CAM users (p = 0.07). Being female and a CAM user was significantly associated with imperfect adherence to anti-hypertensive medication. Older and white British respondents were significantly more likely to report perfect adherence. Blood pressure monitors were used by 67 (43.8%) respondents, which was not associated with gender, CAM use or adherence to medication. Conclusion Hypertensive patients use a variety of self-care methods, including CAM, home blood pressure monitors, and adherence to prescribed medication. This study found the prevalence of CAM use in hypertensive patients was higher than in the UK population. It is important to acknowledge the self-care behaviour of hypertensive patients, in order to assess potential harm, and encourage effective methods of self-care.